2019
DOI: 10.1177/0018726719851835
|View full text |Cite
|
Sign up to set email alerts
|

When performance gets personal: Towards a theory of performance-based identity

Abstract: For better or worse, contemporary society places immense value on achievement and performance. What are the consequences of this emphasis on (if not obsession with) performance for people’s sense of self, and relatedly, their mental health and well-being? We develop a theoretical lens for exploring such questions by introducing the concept of performance-based identity—a form of identity that we propose arises when performance (at work or in another setting) becomes personally meaningful to the extent that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 100 publications
1
11
0
Order By: Relevance
“…Jetten, Postmes, and McAuliffe (2002), for instance, found that the more North Americans identified with their (individualistic) culture, the more likely they were to endorse individualistic attitudes and preferences -a surprising finding in light of traditional social identity principles, which suggest that strong group identification is antithetical to individualism. Findings such as these support the notion that a single identity can simultaneously have both individualizing and socializing psychological consequences (Ashforth, 2007;Vignoles, 2019;Walker & Caprar, 2020), and problematize the notion that social and personal identity exist in an antagonistic relationship.…”
Section: Strengths and Limitations Of A Context-based Framing Of The Spidsupporting
confidence: 52%
See 2 more Smart Citations
“…Jetten, Postmes, and McAuliffe (2002), for instance, found that the more North Americans identified with their (individualistic) culture, the more likely they were to endorse individualistic attitudes and preferences -a surprising finding in light of traditional social identity principles, which suggest that strong group identification is antithetical to individualism. Findings such as these support the notion that a single identity can simultaneously have both individualizing and socializing psychological consequences (Ashforth, 2007;Vignoles, 2019;Walker & Caprar, 2020), and problematize the notion that social and personal identity exist in an antagonistic relationship.…”
Section: Strengths and Limitations Of A Context-based Framing Of The Spidsupporting
confidence: 52%
“…Whilst acknowledging the risks of construct proliferation (e.g., Podsakoff, MacKenzie, & Podsakoff, 2016), this interpretive ambiguity supports the case for a semantic refresh: fresh terms allow for new, more precise meanings that are unmuddied by any earlier interpretations. Second, I assume that an identity is highly meaningful self-knowledge that is used for self-definitional purposes (e.g., Tajfel & Turner, 1979;Walker & Caprar, 2020). I further assume that each individual has myriad identities (Ramarajan, 2014), which move in and out of psychological awareness over time and across contexts (Oakes, 1987), and that each of these identities can vary along myriad dimensions -two of which are the social and personal dimensions.…”
Section: A Dynamic Two-dimensional Conceptualization Of the Social And Personal Dimensions Of Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Conceptualised by Walker and Caprar (2020), the performance-based identity focuses not only on how individuals perceive their way into an identity but also on how well they act, behave, and perform their way into it. It is important to note that the term performance in the present study is not associated with productivity nor the effectiveness constructs as in management research.…”
Section: Literaturementioning
confidence: 99%
“…Keeping track of trackers and tracking poses organizational and individual challenges. Employees place great emphasis on performance and achievement data and how it shapes their identities and well-being (Walker and Caprar 2019). Human resource (HR) functions may lack the various capabilities needed to manage all data analytic interactions and interests between employers and employees (Angrave et al 2016).…”
Section: Introductionmentioning
confidence: 99%